PRE DISASTER COMMUNICATION ON ONLINE NEWS PORTAL TRIBUNNEWS MARCH 2020 EDITION AS DISASTER MANAGEMENT SUPPORT - Chandra Sari, Rohmah Nia; Kriyantono, Rachmat; Dwi Prianti, Desi (Advances in Social Sciences Research Journal, 2021)
Covid-19 has become an issue that has been written about in the media since the end of 2019. Since the emergence of the first case in Indonesia in March 2020, efforts are needed to manage disasters that occur. The role of various parties is needed to provide information and communication to the public, one of which is through the mass media. Information on pre-disaster is important for the formation of security and community capacity in dealing with disasters. The mass media becomes a self-warning system in providing information and education to the public. Currently the media continues to grow, the internet makes it easy for every audience to access various information in the mass media, one of which is disaster information. This study aims to provide an overview of how disaster information is packaged in the mass media as a form of disaster communication to the public. The concepts used in this research are disaster management, and disaster journalism. This research method uses descriptive qualitative using literature studies and framing analysis on the online news portal Tribunnews during March 2020. The results of this study indicate that disaster communication determines community attitudes in dealing with disasters. The role of disaster communication in the mass media is very important, and can determine the success of the government in providing information for public safety and overcoming disasters that occur. This research contributes that the optimization of disaster communication is important in disaster management. The government is the main source of the media in finding news sources. Therefore, the government must provide information intake actively, periodically and with a positive frame.